ANALISIS KESESUAIAN LOKASI DAN DAYA DUKUNG KAWASAN WISATA MANDEH KABUPATEN PESISIR SELATAN - Khairunnisa Maizuwardi; febriandi febriandi (JURUSAN GEOGRAFI FIS UNP, 2020)
Mandeh Tourism Area is one of the conservation centers of small and outermost islands, especially in western Indonesia and a marine ecotourism destination that is mostly visited by tourists. In order for this area to remain sustainable and stable in the use of it’s islands, it is necessary to control and assess the area. The objective study is (1) to determine the suitability of the location and carrying capacity of Mandeh Tourism Area (2) to determine the analysis of the suitability on the location and carrying capacity of Mandeh Tourism Area. This study uses survey methods and weighting of scores to calculate the carrying capacity of the region to maintain the stability the island. The results obtained indicate that the condition of Mandeh Tourism Area is still in good condition, both in terms of characteristics of tourism resources, hydro oceanographic parameters, beach morphology and the condition of the quality of the marine waters in the Mandeh Tourism Area. Based on the results of the study it can be concluded that (1) the condition of the waters in Sutan Island is still good to support a variety of marine ecotourism activities beach recreation of the class category very much in accordance with the percentage of 91.8%, according to the percentage of 80.1 %, according to conditional with a percentage of 61.52%, Swin tourism with class category is very suitable with percentage 89.2% and according to percentage 75.7%. Classified water park attraction tourism are very suitable with a percentage of 96.0%. The carrying capacity of the area for tourism activities in the beach recreation category is 9 people/day, the swimming category is 458 people/day , and the water park attraction tourism is 760 people/day. (2) The condition of the waters of Traju Island is quite good in supporting a variety of marine ecotourism activities beach recreation activities in the class category according to the percentage of 69.86% and according to conditional with a percentage of 55.7%, Swimming tourism with class categories according to the percentage of 69.32%, Water park attraction tourism in the class category is very suitable with a percentage of 93.74%. The carrying capacity of the area for tourism activities in the beach recreation category is 7 people/day, swimming category is 216 people/day, the water park attraction tourism is 102 people/day. (3) The condition of the waters of Cubadak Island (Kapo-kapo) is very supportive in a variety of marine ecotourism activities beach recreation activities class category is very suitable with a percentage of 90.3%, Swimming tourism class category is very in accordance with the percentage of 85.13 %, Water park attraction tourism class category very much in accordance with the percentage of 93.74% and Cubadak Island tourism in the class category very much in accordance with the percentage of 67.8%. The carrying capacity of the area fot tourism activities in the beach recreation category is 16 people/day, swimming category is 1,300 people/day, water park attraction tourism os 1,810 people/day and mangrove tourism is 2,915 people/day.